The reference values in the interpretation of toxicological data - Iavicoli, Ivo; Leso, Veruscka; Fontana, Luca (La Medicina del Lavoro, 2019)
The worldwide gradual expansion of industrialization has led to a dramatic increase in the production and use of chemical substances. This has resulted in a greater dispersion of these elements in the environment and in an increased exposure of the general population and workers. In this scenario, a thorough knowledge of exposure levels is needed in order to assess chemical risks in environmental and occupational settings. Biological monitoring is among the most useful tools for assessing exposure. However, in order to provide really effective guidance in the application/implementation of risk management measures, biomonitoring results need to be compared with appropriate references. Reference values (RVs) are an excellent resource since useful information for a correct interpretation of toxicological data can be obtained by comparing them with biomonitoring results. In the field of public health, this may enable us to identify potential sources of exposure, define the principal and most frequently exploited routes of exposure, and outline chemical absorption. Similarly, in occupational medicine, RVs can be used to give meaning to biomonitoring findings, especially when a biological limit value is not available for the chemical in question. Furthermore, these values are a valid tool for assessing exposure to chemical carcinogens. Therefore, by integrating reference values in an appropriate and complete system of guide values that also includes action levels and biological limit values, we could obtain both an adequate assessment of exposure and a better understanding of toxicological data.